Tuning the basicity of Cu-based mixed oxide catalysts towards the efficient conversion of glycerol to glycerol carbonate - Manikandan, Marimuthu; Prabu, Marimuthu; Kumar, S. K. Ashok; Sangeetha, Palanivelu; Vijayaraghavan, Rajagopalan (Molecular catalysis, 2018)
A series of efficient and robust Cu based mixed oxides were synthesized by a simple co-precipitation method and utilized for the production of glycerol carbonate (GC) via transesterification of glycerol with dimethyl carbonate (DMC). The synthesized materials were characterized using XRD, UV-vis spectroscopy, SEM, TEM, N-2 sorption, CO2-TPD, and XPS. The addition of Cu on Mg/Al mixed oxides exhibits significant changes in its physicochemical properties and catalytic activity. The obtained mixed oxides showed remarkably high transesterification activity towards the efficient conversion of glycerol to GC under economical reaction conditions without using any solvent. Among all the catalysts employed, highest catalytic activity was observed over MAC-0.6 catalyst with glycerol conversion of 96.4% and GC yield of 91.2%. The improved catalytic performance was observed mainly due to the optimized catalyst molar ratio and strong surface basicity. The strong surface basic sites were greatly attributed to the incorporation of Cu2+ cations in the MgAl (O) periclase that efficiently catalyzed the transesterification of glycerol with DMC. Furthermore, the reported catalyst was robust and could be recycled for more than five times without any significant loss in its catalytic activity.

Temperature-controlled hydrothermal synthesis of α-MnO2 nanorods for catalytic oxidation of cyclohexanone - Jha, Ratnesh Kumar; Manikandan, Marimuthu; Prabu, Marimuthu; Vineeth, Nidhi R.; Dharmalingam, Praveen; Archana, Ramakrishnan; Harsha, Murudappa; Shankar, Sonu Ram; Bhatte, Kushal; Raja, Thirumalaiswamy (CHEMPLUSCHEM, 2024)
Keywords: Adipic Acid; conversion; MANGANESE OXIDES